2023
DOI: 10.1002/ejoc.202201419
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Catalyzed Hydroxyl‐Yne Click Reaction: A Powerful Tool toward Red‐Emitting Nontraditional Small Organic Luminogens

Abstract: Nontraditional small organic luminogens (NTSOLs) without classic conjugated chromophores have attracted significant attention. However, the design and synthesis of NTSOLs with fluorescence in the red region remain significantly challenging. In this study, we established a self‐catalyzed hydroxyl‐yne click reaction for preparing long‐wavelength and red‐emitting NTSOLs. Owing to their perfect reaction selectivity, high efficiency, and excellent universality, a series of compounds with well‐defined structures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…NLMs without aromatic groups which exhibit CTE properties are often used for cell imaging due to their low toxicity [ 46 , 47 , 48 , 49 ]. To validate the potential of P1 for cell imaging and labelling applications, we used standard methylthiazolyl diphenyltetrazolium bromide (MTT) assays to evaluate the cytotoxicity of P1 at different concentrations on HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
“…NLMs without aromatic groups which exhibit CTE properties are often used for cell imaging due to their low toxicity [ 46 , 47 , 48 , 49 ]. To validate the potential of P1 for cell imaging and labelling applications, we used standard methylthiazolyl diphenyltetrazolium bromide (MTT) assays to evaluate the cytotoxicity of P1 at different concentrations on HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
“…For example, very recently, Jiang and coworkers found that self-catalyzed hydroxyl-yne click polymerization could be realized in the presence of tertiary amine-containing alcohols, which could serve as both monomers and internal bases during the polymerization process. [123,124] The introduction of nitrogen atoms into alcohol monomers allows this polymerization to occur without an external base catalyst. Furthermore, activated alkynes mentioned above generally result in the partially conjugated polymers by X-yne click polymerizations.…”
Section: Monomer Scope Expansionmentioning
confidence: 99%
“…This allows for the rapid and controlled formation of complex molecular structures with high precision. Moreover, these reactions can be carried out under mild conditions, which minimizes undesirable side reactions and limits the amount of unwanted byproducts. …”
Section: Introductionmentioning
confidence: 99%